2007
DOI: 10.1590/s0034-89102006005000021
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the iron status of pregnant women and their newborns

Abstract: Relationship between the iron status of pregnant women and their newborns Relação entre o estado nutricional de ferro de parturientes e seus recémnascidos ABSTRACT OBJECTIVE: To determine the relationship between iron nutritional status of pregnant women and their newborns using a combination of hematological and biochemical parameters for the diagnosis of iron defi ciency. METHODS: A cross-sectional study was conducted in Jundiaí, Southeastern Brazil, in 2000. Venous blood samples collected from 95 pregnant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 5 publications
2
25
0
6
Order By: Relevance
“…However, studies have shown that inadequate iron status during pregnancy does not cause inhibition of transfer of iron to the baby, if the mother's nutrition is adequate (23). In another study which is similar to our study, no significant difference was found in babies in terms of iron levels at the time of delivery, although half of the pregnant women had iron deficiency and anemia (24).…”
Section: Discussionsupporting
confidence: 75%
“…However, studies have shown that inadequate iron status during pregnancy does not cause inhibition of transfer of iron to the baby, if the mother's nutrition is adequate (23). In another study which is similar to our study, no significant difference was found in babies in terms of iron levels at the time of delivery, although half of the pregnant women had iron deficiency and anemia (24).…”
Section: Discussionsupporting
confidence: 75%
“…However, this variable is not very specific or sensitive 11 . Hemoglobin levels can be altered in different pathologic conditions, such as infectious and inflammatory processes, hemorrhage, protein-caloric malnutrition, associated to medications and smoking 12 .…”
Section: Introductionmentioning
confidence: 99%
“…2 A carência de ferro ocorre no organismo, de forma gradual e progressiva, até que a anemia se manifeste. 3 As gestantes representam um dos grupos populacionais mais vulneráveis às anemias nutricionais, em função da baixa ingestão durante esse período e aumento da demanda deste mineral. Como conseqüên-cia associa-se a uma maior incidência de abortos, partos prematuros, baixo peso ao nascer e morte perinatal, entre outras.…”
Section: Introdução Introdução Introdução Introdução Introduçãounclassified